2018
DOI: 10.1016/j.jgeb.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and PCR-RFLP analysis using Pst 1 and Alu 1 of multidrug resistant Klebsiella pneumoniae causing urinary tract infection in women in the eastern part of Bangladesh

Abstract: Klebsiella pneumoniae is the second leading causative agent of UTI. In this study, a rapid combined polymerase chain reaction and restriction fragment length polymorphism analysis was developed to identify K. pneumoniae in women, infected with urinary tract infection in the Sylhet city of Bangladesh. Analysis of 11 isolates from women at the age range of 20–55 from three different hospitals were done firstly by amplification with K. pneumoniae specific ITS primers. All of the 11 collected isolates were amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Some of the fish pathogens showed scattered sensitivity, whereas augmented drug resistance patterns were observed for human pathogens such as K. pneumoniae and S. aureus; in particular, one K. pneumoniae isolate showed resistance to all ten tested antibiotics. A recent study in Bangladesh found a complete resistance pattern in many K. pneumoniae isolates from the urinary tracts of infected women (Mahmudunnabi et al 2018). The drug sensitivity for other clinical bacteria, such as E. coli and P. aeruginosa, also showed a similar upwardtrending graph similar to that obtained from recently isolated clinical samples in Bangladesh .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Some of the fish pathogens showed scattered sensitivity, whereas augmented drug resistance patterns were observed for human pathogens such as K. pneumoniae and S. aureus; in particular, one K. pneumoniae isolate showed resistance to all ten tested antibiotics. A recent study in Bangladesh found a complete resistance pattern in many K. pneumoniae isolates from the urinary tracts of infected women (Mahmudunnabi et al 2018). The drug sensitivity for other clinical bacteria, such as E. coli and P. aeruginosa, also showed a similar upwardtrending graph similar to that obtained from recently isolated clinical samples in Bangladesh .…”
Section: Discussionsupporting
confidence: 69%
“…A recent study in Bangladesh found a complete resistance pattern in many K. pneumoniae isolates from the urinary tracts of infected women (Mahmudunnabi et al . ). The drug sensitivity for other clinical bacteria, such as E. coli and P. aeruginosa , also showed a similar upward‐trending graph similar to that obtained from recently isolated clinical samples in Bangladesh (Saha et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A total of 35 serial cycles of the amplification reaction were performed in a MultiGene Gradient Thermal Cycler (Labnet International Inc., USA). The PCR products were separated by electrophoresis on an agarose gel, stained with ethidium bromide solution, and visualized in a gel documentation system (8).…”
Section: The Amplification Of the Sfa Genementioning
confidence: 99%
“…Drug resistance in E. coli is one of the most common barriers for treating UTI patients worldwide. However, the problem is more severe in countries like Bangladesh due to an improper tendency of frequently prescribing antibiotics for the treatment of UTIs (8). The multidrug-resistant strains of E. coli have been reported to further add to the complications in the UTI patients and decrease the effectiveness of the treatment (9,10).…”
Section: Introductionmentioning
confidence: 99%